Holm-oak (Quercus ilex subsp. Ballota) acorns infestation by insects in Mediterranean dehesas and shrublands - Leiva, María José; Fernández-Alés, Rocío (Forest Ecology and Management, 2005)
The aim of this study is to know if acorn predation by insects is limiting the sexual regeneration of holm-oak in Mediterranean dehesas and if this process plays the same or a different role in these human-managed ecosystems and in adjacent Mediterranean shrublands which are much less intensively transformed and exploited by man than Mediterranean dehesas. We conducted the study in Southern Spain, in three sites containing dehesas and in three sites containing Mediterranean shrublands and included a total of 90 holm-oak trees (15 holm-oak trees per site) and 4500 acorns (50 acorns per tree). The weevil Curculio elephas and the moth Cydia fagiglandana were the insect species that predated the acorns collected from our sites. The per-tree mean percentage of insect-infested acorns was 16.6% for the whole set of trees included in the study. However, at any given site, variability in the infestation rate among individual trees was very high (i.e., 2–72% and 0–32% infested acorns per tree in the most and less variable sites, respectively). There were signiﬁcant differences in the infestation rate among the studied sites. However, these differences were not related to the ecosystem type as the group of sites that experienced the lowest signiﬁcant infestation rate (10–16% infested acorns per tree in average) were occupied either by dehesas or by shrublands and the same was true for the group of sites that experienced the highest signiﬁcant infestation rate (16–30% infested acorns per tree in average). Infested acorns experienced a 15% decreased in viability (i.e., acorn germination and seedling emergence) comparative to sound acorns. Combining this rate and the mean per-tree average rate of acorn infestation resulted in a 2.5% failures in seedling recruitment due to insect infestation for the whole studied area. We conclude that the effect of pre-dispersive seed predation on seedling recruitment is very low in average, although it likely varies moderately (i.e., from 1.5% to 4.5%) among sites. Current management in dehesas i.e., regular pruning of holm-oak trees and high consumption of the acorn crop by livestock from year to year, does not control pre-dispersive acorn predation by weevils and moths and thus, it does not contribute to explain the poor self-regeneration of the holm-oak trees in these ecosystems comparative to adjacent Mediterranean shrublands.
Keywords: holm-oak self-regeneration; moths; pre-dispersive acorn predation; tree-to-tree variability in acorndry weight and in; weevils

Holm-oak (Quercus ilex subsp. Ballota) acorns infestation by insects in Mediterranean dehesas and shrublands (Forest Ecology and Management, 2005)
The aim of this study is to know if acorn predation by insects is limiting the sexual regeneration of holm-oak in Mediterranean dehesas and if this process plays the same or a different role in these human-managed ecosystems and in adjacent Mediterranean shrublands which are much less intensively transformed and exploited by man than Mediterranean dehesas. We conducted the study in Southern Spain, in three sites containing dehesas and in three sites containing Mediterranean shrublands and included a total of 90 holm-oak trees (15 holm-oak trees per site) and 4500 acorns (50 acorns per tree). The weevil Curculio elephas and the moth Cydia fagiglandana were the insect species that predated the acorns collected from our sites. The per-tree mean percentage of insect-infested acorns was 16.6% for the whole set of trees included in the study. However, at any given site, variability in the infestation rate among individual trees was very high (i.e., 2–72% and 0–32% infested acorns per tree in the most and less variable sites, respectively). There were signiﬁcant differences in the infestation rate among the studied sites. However, these differences were not related to the ecosystem type as the group of sites that experienced the lowest signiﬁcant infestation rate (10–16% infested acorns per tree in average) were occupied either by dehesas or by shrublands and the same was true for the group of sites that experienced the highest signiﬁcant infestation rate (16–30% infested acorns per tree in average). Infested acorns experienced a 15% decreased in viability (i.e., acorn germination and seedling emergence) comparative to sound acorns. Combining this rate and the mean per-tree average rate of acorn infestation resulted in a 2.5% failures in seedling recruitment due to insect infestation for the whole studied area. We conclude that the effect of pre-dispersive seed predation on seedling recruitment is very low in average, although it likely varies moderately (i.e., from 1.5% to 4.5%) among sites. Current management in dehesas i.e., regular pruning of holm-oak trees and high consumption of the acorn crop by livestock from year to year, does not control pre-dispersive acorn predation by weevils and moths and thus, it does not contribute to explain the poor self-regeneration of the holm-oak trees in these ecosystems comparative to adjacent Mediterranean shrublands.

Within-tree variation in transpiration in isolated evergreen oak trees: evidence in support of the pipe model theory (Tree Physiology, 2001)
Within-tree variation in sap flow density (SFD) was measured in two isolated evergreen oak (Quercus ilex L.) trees growing in an oak savannah (dehesa) in southwest Spain. Sap flow was estimated by the constant heating method. Three sensors were installed in the trunk of each tree in three orientations: northeast (NE), northwest (NW) and south (S). Sap flow density was monitored continuously from May 18 to September 27, 1993. Daily values of SFD ranged between 500 and 4500 mm3 mm−2 day−1. There were significant differences in SFD between orientations; SFD was higher in the NE and NW orientations than in the S orientation. These differences were noted on both a daily and seasonal time scale, and were less pronounced on cloudy days and at the end of the drought period, when SFD was relatively low. Our results support the idea that branches of trees can be viewed as a collection of small independent plants.
10.1093/treephys/21.6.409